Uncertainty of timing for global challenges and problems with transition to renewable energies - Yuri Yegorov (European Regional Science Association (ERSA), 2014)
What will come first ? non-acceptable global warming or extinction of oil reserves? Both processes can bring substantial costs to the mankind, but their order has important economic implications. The answer to this question will either lower oil price in the long run or will lead to its further rise. It is very important for Russian economy. From the global perspective, both dangers should be taken into account, and transition to renewable energies is the only remedy for both. However, the optimal speed of this transition depends on temporal dynamics of both threats that is highly uncertain at this moment. The goal of this paper is to review the problems with different renewable energies and to outlay different scenarios for the timing of major impact from global warming and oil peak. The problems with renewable energies have mostly economic origin. The global resources of hydropower are limited. While wind is already cheap, it should be balanced due to stochastic supply. Solar energy also needs to be balanced and is still relatively expensive. Oil products and their liquid renewable substitutes (biofuels) will thus remain an important compliment to electricity in the long run. However, biofuels are competing with agriculture for land, and thus can replace only a limited fraction of energy. The first signs of global warming bring the costs today and it comes as increased frequency of extreme weather phenomena (hurricanes, floods, etc). The rate of temperature increase has some range of uncertainty but it generally accepted that +2 degrees is an acceptable limit, and it might come in the middle of the 21st century. One of the policies to deal with it is not to extract all fossil fuels from the ground. However, it is highly likely that all oil will be extracted before global warming will have severe consequences. Since only biofuels can substitute oil in transport, given the current trend in transportation, peak oil can cause too much demand for biofuels, that will be dangerous for food security. Both the price of oil and biofuels would rise to such level, that current level of transportation will be impossible. This can cause resettlement of people to smaller cities. It is possible to conclude that while renewable energies represent a remedy, full transition will not be easy.
Keywords: Q31; Q42; Q54; 330; renewable energies; transition; problems; global warming; peak oil